Basal cell carcinoma presenting as an excoriated cicatricial plaque: A case report - Emine Müge Acar; Asuman Kilitci; Zeliha Kaya; Ozan Luay Abbas; Funda Kemeriz (Wolters Kluwer Medknow Publications, 2018)
Basal cell carcinoma (BCC) is the most common skin cancer with several clinical and histopathological subtypes. Trauma and scar tissue have been implicated as possible etiological causes of BCC. Here, we report a case of a 37-year-old man with BCC arising on a longstanding cicatricial plaque with nearly 30 years' duration. Intractable pruritus, which had started two months ago and gradually intensified, was the patient's main complaint upon admission. The lesion presented as a linear, erythematous, excoriated cicatricial plaque in the left supraclavicular region. Pearly borders and the mildly atrophic center of the plaque, that were recognized upon close examination, were notable features and may indicate BCC. We believe that a detailed patient history and meticulous clinical examination are essential for diagnosing BCC arising in longstanding scars. Keywords: Scar, Basal cell carcinoma, Pruritus, Malignancy, BCC